2022
DOI: 10.1002/smll.202204109
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Improved Surface and Bulk Participation of Evolved Perovskite Oxide for Boosting Oxygen Evolution Reaction Activity Using a Dynamic Cation Exchange Strategy

Abstract: Figure 10. Electrochemical performance of PBSC and PBSC+Fe exo 3+ characterized by rechargeable Zn-air batteries. a) A schematic of a Zn-air battery, b) open-circuit-voltage profiles, c) discharge-charge polarization curves, d) discharge voltages and the power densities, e) galvanostatic discharge curves, and f) discharge-charge cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…While various perovskite‐based electrocatalysts for OER have been developed with their effective catalytic mechanism, the correlation between surface chemistry and the catalytic mechanism still remains vague. [20,59–61] . In some perovskites, 8‐coordinated A‐site alkaline‐earth metals (such as Sr, Ba) are less stable than the ‘6‐coordinated B‐site transition metals’ which are easily leached out during the OER procedure, resulting in the change (increase or decrease) of catalytic performance of OER [62] .…”
Section: Mechanism Of Perovskite‐driven Oermentioning
confidence: 99%
See 2 more Smart Citations
“…While various perovskite‐based electrocatalysts for OER have been developed with their effective catalytic mechanism, the correlation between surface chemistry and the catalytic mechanism still remains vague. [20,59–61] . In some perovskites, 8‐coordinated A‐site alkaline‐earth metals (such as Sr, Ba) are less stable than the ‘6‐coordinated B‐site transition metals’ which are easily leached out during the OER procedure, resulting in the change (increase or decrease) of catalytic performance of OER [62] .…”
Section: Mechanism Of Perovskite‐driven Oermentioning
confidence: 99%
“…The perovskites offer a unique catalytic regulation with their structural flexibility (by optimizing both surface (e. g., composition) and bulk (e. g., lattice oxygen) properties), further consolidating their candidacy for a sustainable and economical solution for large-scale water-splitting. [61] In 1984, Bockris and Otagawa uncovered the involvement of lattice oxygen in catalytic water oxidation for the first time. They investigated the electronic structure-activity relationship of perovskite oxides towards alkaline OER in detail to conclude that the weakly coordinated lattice oxygen atoms (e. g., LaNiO 3 ) are released from the perovskite framework during the reactivity.…”
Section: Double Perovskite For Electrochemical Oxygen Evolution Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite oxides with an ABO 3 structure have been developed as air electrode materials. Alternative perovskite oxides with mixed ion and electron conduction (MIEC) have been employed for O-SOFCs and H-SOFCs. The MIEC allows the ORR active site to diffuse over the entire surface of the cathode to enhance ORR activity. SrCoO 3−δ -based materials have received much attention owing to their superior oxygen ionic and electronic conductivity. Nevertheless, the chemical stability and thermal matching of these materials are not very satisfactory. …”
Section: Introductionmentioning
confidence: 99%
“…Among the alternative non-precious oxide electrocatalysts, perovskite oxides (ABO 3 ) are recognized as the superior ones. , In addition to low cost, perovskite oxides have other apparent benefits, such as their structure and composition flexibility. A significant number of investigations have recently demonstrated that perovskite oxides have prominent activity and good stability. Particularly, the intrinsic activity has been associated with the orbital electron filling (e g ) and the covalency between B and O of ABO 3 .…”
Section: Introductionmentioning
confidence: 99%